2015
DOI: 10.1063/1.4931673
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulations and lattice dynamics determination of Stillinger-Weber GaN thermal conductivity

Abstract: The bulk thermal conductivity of Stillinger-Weber (SW) wurtzite GaN in the [0001] direction at a temperature of 300 K is calculated using equilibrium molecular dynamics (EMD), non-equilibrium MD (NEMD), and lattice dynamics (LD) methods. While the NEMD method predicts a thermal conductivity of 166 6 11 W/mÁK, both the EMD and LD methods predict thermal conductivities that are an order of magnitude greater. We attribute the discrepancy to significant contributions to thermal conductivity from long-mean free pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Therefore, no matter what expression is used in the fit, using NEMD data with relatively short simulation cell lengths may result in significant errors and is a possible reason for some reported inconsistencies between the EMD and NEMD methods. Recently, Liang et al [18] found that the extrapolated κ 0 obtained by using the linear fit to their NEMD data with L x ≤ 150 nm is 166 ± 11 W m −1 K −1 for bulk GaN (described by a SW potential) at 300 K, which is several times smaller than their EMD value, 1190 ± 85 W m −1 K −1 . They also attributed the inconsistency between the NEMD and EMD predictions to the inadequacy of the linear extrapolation.…”
Section: A 3d Bulk Siliconmentioning
confidence: 87%
“…Therefore, no matter what expression is used in the fit, using NEMD data with relatively short simulation cell lengths may result in significant errors and is a possible reason for some reported inconsistencies between the EMD and NEMD methods. Recently, Liang et al [18] found that the extrapolated κ 0 obtained by using the linear fit to their NEMD data with L x ≤ 150 nm is 166 ± 11 W m −1 K −1 for bulk GaN (described by a SW potential) at 300 K, which is several times smaller than their EMD value, 1190 ± 85 W m −1 K −1 . They also attributed the inconsistency between the NEMD and EMD predictions to the inadequacy of the linear extrapolation.…”
Section: A 3d Bulk Siliconmentioning
confidence: 87%
“…Here, simulations were repeated with different heat exchanges (J = 9.5 -18 eV•ps -1 ). Cross-plane and in-plane thermal conductivities, denoted in the following with superscript symbols ⊥ and ||, respectively, were measured perpendicular and parallel to the interfaces along [ ] Scaling effects on thermal conductivity computed from MD simulations, particularly the differences between NEMD and equilibrium (EMD) methods, have received considerable attention in the literature [40,42,43]. For the NEMD method, a sizeindependent thermal conductivity is usually obtained by performing a linear extrapolation from multiple systems of different length [40].…”
Section: Methodsmentioning
confidence: 99%
“…Scaling effects on thermal conductivity computed from MD simulations, particularly the differences between NEMD and equilibrium (EMD) methods, have received considerable attention in the literature [40,42,43]. For the NEMD method, a sizeindependent thermal conductivity is usually obtained by performing a linear extrapolation from multiple systems of different length [40].…”
Section: Methodsmentioning
confidence: 99%
“…This was also found by Liang et al using the nonequilibrium molecular dynamic method. 33 Results in Fig. 6(a) indicate that the anisotropy is reduced with decreasing film thickness and even disappear when the size effect is very strong.…”
Section: B Out-of-plane Of Gan Thin Filmmentioning
confidence: 91%